Calcium Fructoborate Prevents Skin Cancer Development in Balb-c Mice: Next Part, Reverse Inflammation, and Metabolic Alteration - Kisacam, Mehmet Ali; Kocamuftuoglu, Gonca Ozan; Ozan, Ibrahim Enver; Yaman, Mehmet; Ozan, SemaTemizer (Springernature, 2021)
Metabolic alterations and inflammation are regarded as hallmarks of cancer. Glycolytic flux and intermediate accumulation lead to the production of building blocks and NADPH which is important in protecting the cell from oxidative damage. Inflammation causes the release of mediators responsible for regulating molecular mechanism affecting metabolic pathways. CaFB due to its cis-diol-rich feature may have the potential to interact with molecules taking part in cancer development. This study was aimed to investigate the effects of CaFB on metabolic alterations and inflammation in 7,12-dimethylbenz(a)anthracene (DMBA)/12-O-tetradecanoylphorbol-13-acetate (TPA)-induced skin cancer. For this purpose, 92 Balb-c mice were distributed into 6 groups as control, CaFB, DMBA/TPA (D-T), treatment 1 (T1), 2 (T2), and 3(T3). Apart from control and CaFB in other groups, tumors initiated with 97.5-nmol DMBA and 6.5-nmol TPA. Treatment groups received 3 mg/kg/day CaFB with DMBA (T1), with TPA (T2), and after tumor formation (T3). In the D-T group, glyceraldehyde-3-phosphate dehydrogenase (GAPDH) activity, 6-phosphogluconate dehydrogenase (PGD), glutathione (GSH), interleukin 6 (IL-6), (IL-1 beta), tumor necrosis factor-alpha (TNF-alpha) levels increased (p < 0.001) while malondialdehyde (MDA) levels decreased (p < 0.001) compared with that in control. CaFB application ameliorated DMBA-TPA effect according to the distribution time. It is noteworthy to consider CaFB as a potential preventive agent in skin cancer development.
Keywords: Calcium fructoborate; Skin cancer; Glyceraldehyde-3-phosphate dehydrogenase; 6-Phosphogluconate dehydrogenase; Inflammation; Oxidative stress